Peran Media dalam Strategi Pemasaran Digital Berbasis Konten Tiktok Menurut Hukum Islam - Khoirul Anwar; Adibbatus Silfiyah; Sela Anggraini; Nailul Fauziyah (AL-MANSYUR: Jurnal Ekonomi Syariah, 2026)
This research aims to comprehensively analyze the role of the TikTok platform as a digital marketing strategy instrument within the framework of Islamic law (Fiqh Muamalah). Amidst massive economic digitalization, TikTok—through its For You Page (FYP) algorithm, Live Shopping features, and Affiliate system—has revolutionized the interaction between sellers and buyers. However, the penetration of this technology brings serious ethical implications, ranging from the potential for gharar (uncertainty) in visual descriptions to violations of muru’ah (honor/modesty) in creative content. Employing a descriptive-qualitative method through a literature study of seven key references, this research finds that TikTok marketing is fundamentally aligned with Sharia principles, provided it fulfills the pillars of honesty (shiddiq), transparency (tabayyun), and fairness in information distribution. This study recommends a digital marketing framework that is not solely profit-oriented (economic falah) but also grounded in theological values to achieve blessing (barakah) in muamalah within the cyber era.